Parental perception of neonatal care in urban slums of Jammu city - Dhar, Sharvil; Gupta, Ravinder K. (International Journal of Contemporary Pediatrics, 2024)
Background: India is undergoing rapid urbanization and many rural residents relocate to urban regions in search of employment, better living conditions and access to education and health care facilities. Neonatal morbidity and mortality are attributed to misperceptions in the community about newborn care. In many parts of urban slums in India, care seeking from multiple providers and use of traditional/home remedies hampered appropriate and timely medical care seeking. Aim was to study awareness, knowledge and practice of newborn care among postnatal mothers in Urban slums of Jammu city. Methods: This observational study was conducted in Urban slums of Jammu city. A total of 100 mothers of newborns residing in urban slums participated in the study after taking Informed Consent from them. A self-structured proforma was used to collect data. Results: Most of the deliveries were conducted in hospital (82%) and 18% were home deliveries. Regarding newborn care practices 88 % had wrapped the newborn with clean cloth immediately after birth. 58% of newborns were given first bath within 2-7 days. 39% of mothers-initiated breast feeding within 6-24 hours. Majority (68%) newborns were fed with colostrum. Regarding cord cutting procedures among home deliveries, it was observed that clean blade was used in 15 newborns while in 3 cases aseptic practice for cord cutting was not followed. Conclusions: Good newborn practices like promotion of warmth, cord care, hygiene and early breastfeeding should be the main focus of community-based health workers. The present study concluded that some unhealthy neonatal care practices were still found to be prevalent which can be mitigated by increasing awareness among parents through IEC activities.